The Psychology of Beauty : Creation of a Beautiful Self. - Sinkman, Ellen (Jason Aronson, Inc., 2012)
The Psychology of Beauty: Creation of a Beautiful Self, by Ellen Sinkman, LCSW, addresses the vital importance of beauty, its sources, and manifestations in everyone's lives-including psychotherapy patients. During psychotherapy, patients manifest or defend against the strong desire to be beautiful. This book considers definitions of beauty, gender identity themes, and origins of beauty in the mother-infant relationship. It investigates ugliness, sado-masochistic beauty pursuits, evolutionary factors, and aspects of aging. Sinkman highlights emerging clinical material which has yet to gain not.